(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the pedagogical and psychological significance of a teacher’s creativity in the formation of primary school students as individuals. In the modern education system, the priority task is not only to impart knowledge, but also to reveal the student’s internal potential, to form independent and critical thinking skills in him. The article scientifically and practically substantiates the effectiveness of the teacher’s creative approaches in the teaching process - creating non-standard situations, game technologies and project-based learning methods. The article also discusses the impact of the teacher’s creative potential on the social adaptation and spiritual development of students. The analysis conducted during the research shows that students studying in a creative environment demonstrate higher cognitive activity and emotional stability compared to the traditional form of teaching. At the end of the article, practical recommendations are given for primary school teachers to improve the effectiveness of the lesson.